Impact of the Cmos Pixel Clock on Optical Camera Communication Using Rolling Shutter Mode - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2024)
This study delves into the impact of the pixel clock (p_{\text{clk}}) on the frequency response of Optical Camera Communication (OCC) systems utilizing rolling shutter mode. Employing an experimental approach, we examine how variations in the p_{\text{clk}} influence the frequency response of a complementary metal-oxide-semiconductor (CMOS) image sensor within OCC links. Our setup incorporates an algorithmic methodology to manipulate and assess internal camera parameters, focusing on the minimum exposure times to optimize signal capture and processing. The findings reveal a direct relation between the p_{\text{clk}} and the achievable frame rate. It is a first approach to delineating its effect on the temporal resolution and bandwidth of the communication channel, showing the importance of these insights for enhancing the design and efficiency of OCC systems. Our research contributes to understanding the hardware limitations and opens future explorations into maximizing the communication performance. © 2024 IEEE.